Kajian Kapasitas Saluran Pada Sistem Jaringan Drainase Untuk Mengatasi Genangan Pada Wilayah Telkom Dan Pasar Buah (Jalan Sudirman Pekanbaru) - Fahrul Iswar; Mudjiatko Mudjiatko; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
This study analyzed drainage capacity, conducting drainage  flow patterns  that affect  the Sago River,  to  cope with  floodwaters  in the  area of  the intersection of  Jalan  Sudirman-Jalan Hang Tuah (Office Telkom) and Pasar Buah, Pekanbaru, and calculate the flow rate when the  rainfall  intensity  high. The data  required  in  this study  conducted  in two ways, namely  field surveys  and  institutional  surveys.  Hydrological  analysis  was conducted to determine  the intensity of  the rain,  in the form of daily rainfall data  for 15 years  (1997-2011).  From the analysis of  the plan  obtained  daily  rainfall  (R24)  for the  5-year anniversary  when  the  study  area  is  126.798  mm.  Tackle the problem  at the point of flooding Pasar Buah can be done by adding dimension to channel SD SG KR2 with added height channel (H) between 5-50 cm. Tackle the problem of flooding at the point of Telkom can be done by adding dimension  to channel SD SG KR5 with added height channel  (H) between 15-50 cm and channel SG AS KR1 with added height channel (H) between 15-50 cm. Keywords: drainage, flow pattern, flow, flood